Geminivirus C4: Interplaying with Receptor-like Kinases. (December 2018) - Zeng, Runxiu; Liu, Xiaoshi; Yang, Chengwei; Lai, Jianbin
Abstract : Geminivirus infection results in systemic symptoms in plants, but the mechanism by which the virus affects cell-to-cell signalling involved in development and resistance remains unclear. Based on recent evidence, we suggest a potential mechanism that geminivirus C4 proteins interfere with intercellular signals by interacting with receptor-like kinases on the plasma membrane.